LOCAL OPEN GOVERNMENT: CASE IN SOUTH COTABATO - Afandi, Syed Agung; Erdayani, Rizki; Afandi, Muslim (Jurnal Administrative Reform, 2024)
This research aims to analyze open government trends and policies in South Cotabato. A qualitative approach, the bibliometric analysis method, and the content analysis method were used in this research. Research data comes from Scopus, Web of Science, Semantic Scholar, Crossref, and South Cotabato policy documents. This research found 127 relevant articles, 683 citations, 13 h-index, and 24 g-index, which show that the South Cotabato open government study has a high impact and productivity. There are 2646 total link strengths, 668 occurrences, 103 topics, and 9 clusters in this study. Access information, public participation, open legislation, public access, public service, infrastructure, public monitoring, public information, information openness, and extractive are the topics that dominate. Meanwhile, potential research topics are public service, service quality, access, public information, communication, interactive, information openness, information quality, accountability, monitoring, and evaluation. Currently, South Cotabato is focused on commitments to open legislation, public participation in extractives, public monitoring of infrastructure, and access to information. These commitments have the potential to make South Cotabato more open.